Analisis Penyebab Kecacatan Dengan Menggunakan Metode Seven Tools Pada Proses Perakitan Mesin Sepeda Motor - Darmawan, Marten; Soewono, Arka Dwinanda; Wijaya, Nickolas Dario; Bachri, Karel Octavianus (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
PT. SMT is a company that manufactures and distributes motorbikes. One of the main products assembled by PT. SMT is a 160 cc motorcycle engine. To improve the quality of the motorbike engine assembly process at PT. SMT, quality management based on the Seven Tools method has been performed. The check sheet analysis based on the production data from the January-July 2023 period shows that the most frequent quality issues in the engine assembly process are dirt on the cylinder inlet valve (64, 2%), followed by rust on the cylinder head (26.1%) and dirt on the gasket cover components for the cylinder head (9.8%). Root cause analysis using the Fishbone diagram finds that work environment factors including dirty workstations, equipment and components, as well as human factors are the main causes of product defects. From this analysis, the recommended improvements include implementing routine cleaning procedures for the work environment, equipment, and components, as well as providing additional training to improve operator competency and foster a better work culture.